Anti-fog heat-resistant polyurethane optical resin and preparation method thereof
By using a copolymer of acryloylureamin and acryloylglycine as polymer additives in polyurethane optical resins, the problem of insufficient fogging and heat resistance in high temperature and high humidity environments is solved, and good anti-fog heat resistance and optical properties are achieved.
Patent Information
- Application Number
- CN202310000478.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-01-03
AI Technical Summary
Polyurethane optical resin is prone to fogging in high temperature and high humidity environments, affecting light transmission, and its heat resistance is poor, which limits its application field.
A copolymer obtained by polymerization of acryloylureamin and acryloylglycine is used as a polymer additive, and a polyurethane optical resin having improved antifog performance and heat resistance is formed by combining with components such as isocyanate and polymer thiol compounds.
It significantly reduces the water contact angle of the resin, increases the glass transition temperature, enhances the anti-fog and heat resistance, and does not affect the transmission ratio and yellowness index of the optical resin.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the field of optical resin materials, and in particular relates to an anti-fog and heat-resistant polyurethane optical resin and a preparation method thereof. Background Art
[0002] Polyurethane materials have a wide range of applications, such as coatings, adhesives, etc. As the types of isocyanate monomers containing NCO groups continue to increase, polyurethane optical resins are also developing. Compared with unsaturated polyesters and polycarbonates (PC), the most important feature of polyurethane (PU) materials is that they have a higher refractive index, such as 1.60 or 1.67, or even up to 1.71. Therefore, functionalizing polyurethane optical resins is an important research direction. .
[0003] The fogging phenomenon on the surface of optical resins is caused by the fact that water vapor condenses into water droplets when it encounters a cold lens in a high temperature and high humidity environment. On the other hand, when the temperature drops, the tiny droplets cool to their dew point, the water vapor reaches saturation, and fog forms on the surface of the lens. The presence of water droplets or fog will refract and scatter light, thereby changing the optical properties of the lens surface, affecting light transmittance, causing the lens to become opaque, and causing visual impairment to the wearer of the lens. The demand for anti-fog optical resins has risen significantly.
[0004] In principle, there are three main measures for resin anti-fogging. The first is to enhance the hydrophilicity of the resin surface, reduce the water contact angle, spread the water droplets on the surface of the gel, reduce optical refraction or scattering, and ensure the transparency of the material. The second is to increase the surface hydrophobicity so that the water droplets slide down under the action of gravity after condensation. The third is to increase the surface temperature above the dew point, such as adding a heating device to the car windshield to slow down the condensation of water droplets. In practical applications, the current methods for improving the anti-fogging performance of lenses in the optical field mainly include surface coating of anti-fog coatings, surface coating of anti-fog films, and optimization of resin synthesis monomers. Anti-fog coatings can be divided into hydrophobic anti-fog coatings (θ>90°, liquid does not wet solids) and hydrophilic anti-fog coatings (θ<90°, liquid can wet solids) according to the principle.
[0005] Patents CN112778900 and CN106336853 both report the preparation formula of anti-fog coating (anti-fog agent). Although anti-fog performance can be achieved in a short time, the anti-fog effect of the lens is poor after long-term use and needs to be re-coated. Patent CN107490814 publicly reports the production process of preparing anti-fog lenses by coating anti-fog agents, which specifically includes the preparation of anti-fog agents, dripping of anti-fog liquid, baking and cooling. Patent CN112946920 publicly reports the coating of a nano super-hydrophilic anti-fog film layer on the surface of a resin, specifically by dipping, spraying, or wiping the surface of the activated resin lens with a nano super-hydrophilic anti-fog coating, and then placing it in a clean constant humidity space to stand and dry, and further placing it in an oven to bake to achieve film curing. Although the coating process can achieve anti-fog performance for a longer time than coating an anti-fog coating, the compatibility of the film layer with the resin and the processing conditions are selective for resin lenses. Because the thermal expansion coefficients of the film layer and the resin are inconsistent and very different, film cracks will occur after coating, causing the film coated on the resin lens to fall off, so multi-layer coating is required for a gradual transition.
[0006] The glass transition temperature of polyurethane optical resin is limited by the characteristics of the resin material, and the temperature is generally between 80 and 110°C. Compared with PC optical materials, although the refractive index of polyurethane optical resin is higher, its heat resistance is poor. In order to better expand the application field of polyurethane optical resin, its heat resistance needs to be improved. Summary of the invention
[0007] To solve the above problems, the object of the present invention is to provide an anti-fog heat-resistant polyurethane optical resin and a preparation method thereof.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] The invention discloses an anti-fog heat-resistant polyurethane optical resin, comprising the following components: isocyanate, a polythiol compound, a polymer auxiliary agent, a catalyst, an ultraviolet absorber and a release agent, wherein the polymer auxiliary agent is a copolymer obtained by polymerization reaction of acrylamide urea (NASC) and acrylamide glycine (ACG).
[0010] The addition of polymer additives can improve the anti-fog performance and heat resistance of the resin.
[0011] The preparation of the polymer auxiliary agent realizes the copolymerization of acryloylureaamine (NASC) and acryloylglycine (ACG) under the action of a free radical initiator to obtain a copolymer of polyacryloylureaamine-acryloylglycine (PNASC-PACG). This copolymer is added to the raw material composition. In the subsequent resin curing process, some carboxyl groups and amides in PNASC-PACG can be chemically bonded with the NCO group, enhancing the interaction between the polymer auxiliary agent and the resin matrix, forming a three-dimensional cross-linked network structure, and improving the thermal properties of the resin. The remaining unreacted carboxyl groups and amides in PNASC-PACG can improve the hydrophilicity of the resin. At the same time, both monomers of acryloylglycine and acryloylureaamine have a double hydrogen bond structure, and the ureaamine group can increase the hydrogen bond donor, and the hydrogen bonding effect further significantly improves the hydrophilicity of the resin. In summary, the PNASC-PACG polymer auxiliary agent effectively gives the polyurethane optical resin good anti-fog performance and heat resistance.
[0012] The structural formula of the acryloyl ureaamine described in the present invention is as follows:
[0013]
[0014] The acryloyl ureaamine is prepared by reacting ureaamine hydrochloride with acryloyl chloride. The specific synthesis route is referenced in patent CN112521625A.
[0015] The structural formula of acryloylglycine described in the present invention is as follows:
[0016]
[0017] The acryloyl glycine is prepared by using glycine and acryloyl chloride as raw materials according to the method of reference Rapid self-healing hydrogels, PNAS 2012, 12, 4383-4388 and patent CN106397646A.
[0018] The structure of the PNASC-PACG polymer additive obtained by polymerization of the above two monomers is as follows:
[0019]
[0020] n is the degree of polymerization, and the range of n is 10-800, preferably 120-400.
[0021] In the present invention, the molar ratio of acryloyl ureaamine to acryloyl glycine in the polymer additive is 1:10-10:1, preferably 1:6-6:1, and more preferably 1:3-3:1.
[0022] The synthesis reaction temperature of the polymer auxiliary agent is room temperature, the pressure is normal pressure, and the polymerization reaction time is 2-6 hours, preferably 3-5 hours.
[0023] The free radical initiator is an organic peroxide compound initiator or an azo compound initiator or a redox system initiator or a photosensitive initiator. The organic peroxide compound initiator is selected from dibenzoyl peroxide (BPO) or peroxydicarbonate, the azo compound initiator is selected from azobisisobutyronitrile (AIBN) or azobisisoheptanenitrile (ABVN), the redox system initiator is selected from an organic oil-soluble redox system formed by a peroxide acyl compound and a tertiary amine compound, and the photosensitive initiator is selected from the photoinitiator IRGACURE-2959 (CAS No.: 106797-53-9). Further preferably, the free radical initiator is IRGACURE 2959, which is initiated under ultraviolet light irradiation conditions. The amount of the initiator is 1%-3% of the total mass of the acryloyl urea amine and acryloyl glycine monomers, preferably 1.5-2.5%. In order to better promote the polymerization reaction of the monomers, the illumination time is 40 minutes.
[0024] In the present invention, the addition amount of the polymer auxiliary agent is 0.1wt%-10wt%, preferably 2wt%-8wt%, more preferably 3wt%-6wt%, based on the total weight of the isocyanate and the polythiol compound.
[0025] The isocyanate used is not particularly limited. As a specific example of the isocyanate component, it can be selected from aliphatic, alicyclic or aromatic isocyanates, such as but not limited to toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, naphthalene diisocyanate, dimethylbiphenyl diisocyanate, 1,4-cyclohexane diisocyanate, p-phenylene diisocyanate, tetramethyl-m-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, xylylene diisocyanate, cyclohexane dimethylene diisocyanate, and a combination of one or two or more of the isocyanate, preferably xylylene diisocyanate or cyclohexane dimethylene diisocyanate, more preferably xylylene diisocyanate.
[0026] The polythiol compound used is not particularly limited. Specific examples of the polythiol compound include, but are not limited to, ethylene glycol dithioglycolate, 1,2-bis(2-mercaptoethoxy)ethane, di(thioglycolate)-1,4-butylene glycol, trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(2-mercaptoacetate), pentaerythritol tetrakisthioacetate, 2,3-dithio(2-mercapto)-1-propanethiol, pentaerythritol tetrakis(3-mercaptopropionic acid) and a combination of one or two or more thereof, preferably 2,3-dithio(2-mercapto)-1-propanethiol or pentaerythritol tetrakis(3-mercaptopropionic acid), and more preferably 2,3-dithio(2-mercapto)-1-propanethiol.
[0027] In order to improve the reaction degree of the functional groups, the molar ratio of NCO group / SH group in the isocyanate component and the polythiol compound needs to be controlled within the range of 0.8-1.5, preferably 0.9-1.1.
[0028] The catalyst is a common organic metal catalyst for the reaction of NCO and SH, including carboxylates, metal alkyl compounds, etc., and the metal elements contained mainly include tin, potassium, lead, mercury, zinc, etc., preferably tin metals. As a specific example, dialkyl tin halides such as dibutyltin dichloride and dimethyltin dichloride, dialkyl dicarboxylates such as dimethyltin diacetate, dibutyltin dioctoate, and dibutyltin dilaurate, preferably dibutyltin dichloride. Based on the total mass of the isocyanate component and the polythiol compound, the added amount of the catalyst can be 0.01-2.0% by weight, preferably 0.015 to 1.0% by weight.
[0029] The organic products selected as ultraviolet absorbers are mainly divided into benzophenones, triazines and benzotriazoles, among which benzophenones have weak absorption and triazines have poor stability, so benzotriazoles are often used for industrial production. Taking benzotriazoles as an example, benzotriazole ultraviolet absorbers, specifically UV 49, UV326, UV 327, UV 360, UV 380, UV 329, preferably UV 329 (trade name Tinuvin 329), can be added in an amount of 0.01 to 2.0% by weight, preferably 0.03 to 1% by weight, based on the total mass of the isocyanate component and the polythiol compound.
[0030] Due to the special requirements of optical resins for light transmittance, a phosphate-based release agent such as an internal release agent with the brand name ZelecUN (manufactured by Sigma-Aldrich or Stepan) is selected as an optical resin release agent. Based on the total mass of the isocyanate component and the polythiol compound, the added amount can be 0.01 to 3.0 weight %, preferably 0.08 to 1.0 weight %.
[0031] Another object of the present invention is to provide a method for preparing an anti-fog heat-resistant polyurethane optical resin: the above-mentioned polymer additives, one or more isocyanates, one or more polythiol compounds, catalysts, ultraviolet absorbers, and release agents are uniformly mixed at room temperature, and the optical resin is obtained after vacuum degassing and temperature curing.
[0032] Preferably, in the preparation method, the raw materials are mixed and filtered through a filter membrane (the pore size of the filter membrane is preferably 0.8μm-1.2μm), and then injected into a special mold for lens processing. They are degassed for 0.5-1.5 hours at room temperature and a pressure of ≤2kPa, and then restored to normal pressure. They are then slowly heated from low temperature to high temperature for curing, for example, the temperature is raised from room temperature to 120°C, and the heating rate is set to 0.1-0.2°C / min to polymerize and cure. When the temperature reaches 100-130°C, it is maintained for 1-3 hours, and the sample is naturally cooled to room temperature. After secondary curing at room temperature for 24-72 hours, it is demolded to obtain an optical material.
[0033] The curing and demoulding of the optical polyurethane resin can be carried out by methods known in the prior art, and the present invention does not make any particular limitation thereto.
[0034] The above polyurethane optical resin is applied in the field of anti-fog optical resin materials.
[0035] The positive effect of the present invention is that the water contact angle of the prepared anti-fog and heat-resistant polyurethane optical resin can be reduced to as low as 11° and the glass transition temperature is significantly increased by 10°C-40°C, the anti-fog and heat-resistant effects are good, and the transmittance and yellowness index (YI) of the optical resin are not negatively affected. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 : Example 1 1H-NMR nuclear magnetic spectrum of PNASC-PACG after polymerization of monomer acryloyl urea amine NASC and monomer acryloyl glycine ACG.
[0037] Figure 2 : Absorption spectrum of the anti-fog and heat-resistant polyurethane optical resin in Example 1. DETAILED DESCRIPTION
[0038] The present invention is further illustrated by the following examples, but the scope of protection of the present invention is not limited thereto.
[0039] The following examples of the present invention will be analyzed and characterized using the following instruments.
[0040] H-NMR spectrum analysis: The H-NMR spectrum characterization of polymer materials is performed with the help of Varian INOVA H-NMR instrument (500 MHz). Take 5-10 mg of sample solvent and dissolve it in deuterated dimethyl sulfoxide (DMSO). After the solution is mixed evenly, use NMR spectrometer to perform 1H-NMR test.
[0041] Gel Permeation Chromatography Analysis: Gel permeation chromatography characterization of copolymer macromolecules was performed using an Agilent 1260 high performance liquid gel permeation chromatograph. The sample was dissolved in tetrahydrofuran (THF) to prepare a solution with a concentration of 5 mg / mL, and tested on the GPC instrument at an elution rate of 1 mL / min and room temperature.
[0042] Analysis of optical resin application indicators: Light transmittance is measured by Hunterlab USVIS 1839 colorimeter, the test light source is C / 2 light source, the test mode is total transmission, and the average transmittance in the wavelength range of 380nm to 780nm is taken as the sample transmittance. In addition, the yellowness index (YI value) of the sample is tested in the same mode.
[0043] The thermodynamic properties of the resin are based on the glass transition temperature Tg of the resin. The glass transition temperature Tg is tested using a Mettler-Toledo high pressure differential scanning calorimeter (METTLER HP DSC1). The DSC test method is: 30°C-300°C, temperature scan, heating rate 10°C / min, nitrogen atmosphere, nitrogen flow rate 50ml / min; each sample is tested 3 times in parallel and the average value is taken.
[0044] Water contact angle test: The water contact angle of the anti-fog and heat-resistant resin was measured using the automatic contact angle measuring instrument DSA-X plus produced by Beto Scientific Instruments Co., Ltd.
[0045] The test of the anti-fog performance of the resin refers to the national standard GBT 31726-2015 Plastic Film Anti-fog Test Method, and combined with the use environment of the optical resin, the test method is divided into the cold fog method and the water bath hot fog method. The specific cold fog method is: inject a certain amount of grade 3 water that meets the requirements of GB / T6682-2008 into the beaker, then buckle the synthetic optical resin on the mouth of the beaker, and then place the optical resin and the beaker together in a refrigerator refrigerated environment (3±2℃), time for 5 minutes, then only take out the optical resin and place it on the standard logarithmic visual acuity chart in Appendix B of GB11533-2011, align the center of the resin with the 0.1 center line of the visual acuity chart, and observe the resin surface from top to bottom under natural light or 40W fluorescent lamp, and complete the observation within 5 seconds. The water bath hot mist method is as follows: inject a certain amount of grade 3 water that meets the requirements of GB / T6682-2008 into a beaker, then buckle the synthesized optical resin on the mouth of the beaker, and then place the optical resin and the beaker together on a heated stirring plate at 60°C, time for 15 minutes, then take out only the optical resin and place it on the standard logarithmic visual acuity chart in Appendix B of GB11533-2011, align the center of the resin with the 0.1 center line of the visual acuity chart, and observe the resin surface from top to bottom under natural light or a 40W fluorescent lamp, and complete the observation within 5 seconds. The test results of these two methods are graded according to different states, specifically divided into 5 levels, as described in the following table.
[0046] Anti-fog level comparison table
[0047]
[0048] The samples of the polyurethane optical resin prepared in the following examples are all prepared by a fixed mold (the fixed mold is a flat-bottomed glass cup with a bottom diameter of 500 mm and a height of 800 mm).
[0049] The NASC used in the following examples were prepared by the following synthesis method (reference patent CN 112521550A), specifically: 13 g of ureaamine hydrochloride was dissolved in 20 mL of deionized water, 70 mL of 2 mol / L K 2 CO 3 solution, then add 40mL of ether, and then add ether solution (50mL) of acryloyl chloride (10mL) dropwise. After the addition is complete, react for 5h in an ice bath. After the reaction is complete, filter and wash the obtained precipitate with water, then dissolve it in hot water and freeze-dry to obtain the product acryloyl ureaamine (NASC).
[0050] The following is that the ACG used in the examples is prepared according to the reference Rapid self-healing hydrogels (PNAS 2012, 12, 4383-4388), the synthesis and swelling properties of poly N-acryloyl glycine hydrogel (doi: 10.3969 / j.issn.1671-7627.2009.06.006) and the method mentioned in patent CN106397646A. The synthesis method is specifically as follows: add 7.5g glycine, 8.8g NaOH and 50ml pure water to a three-necked flask with a stirrer and a constant pressure dropping funnel, turn on the stirring and place the three-necked flask in an ice water bath, and control the temperature to 0°C. Then slowly add 9.0ml acryloyl chloride, and continue to react in the ice water bath for 2h after the addition is completed. After that, adjust the pH to 1-2 with a 6mol / L hydrochloric acid solution, extract with ethyl acetate, and collect the organic phase. The organic phase was further dried by adding anhydrous MgSO4, filtered, and the filtrate was subjected to a rotary evaporator to obtain a solid. Finally, the solid was recrystallized and purified with ethyl acetate to obtain the ACG monomer.
[0051] Note: Since NASC and ACG were used multiple times, they were prepared multiple times in the examples.
[0052] The main raw materials are: m-xylylene diisocyanate (XDI, NCO content is 44.7%, purity ≥99.5%, Wanhua Chemical), cyclohexane dimethylene diisocyanate (H 6 XDI, NCO content is 43.3%, purity ≥ 99.7%, Wanhua Chemical), hexamethylene diisocyanate (HDI, NCO content is 49.8%, purity ≥ 99.5%, Wanhua Chemical), isophorone diisocyanate (IPDI, NCO content is 37.8%, purity ≥ 99.5%, Wanhua Chemical) polythiol compound selected 2,3-dithio (2-mercapto) -1-propanethiol (trade name polythiol 504, purity ≥ 96%, Jingbo Chemical), tetrakis (3-mercaptopropionic acid) pentaerythritol ester (trade name polythiol 405, purity ≥ 96%, Jingbo Chemical), catalyst is dibutyltin dichloride (DBC, purity 96%, Sigma-Aldrich), internal release agent (trade name Zelec UN, Sigma-Aldrich, purity 98%), ultraviolet absorber UV-329 (trade name TINUVIN 329, purity 98%, Shanghai Aladdin Biochemical Technology Co., Ltd.), acryloyl chloride (purity ≥96%, Shanghai Aladdin Biochemical Technology Co., Ltd.), anhydrous potassium carbonate (purity ≥99%, Shanghai Aladdin Biochemical Technology Co., Ltd.), IRGACURE-2959 (Sigma-Aldrich, purity 98%).
[0053] Example 1
[0054] An anti-fog and heat-resistant polyurethane optical resin containing 5 wt % PNASC-PACG copolymer (the monomer molar ratio of NASC to ACG is 1:2) was prepared.
[0055] (1) Synthesis of PNASC-PACG polymer additive
[0056] Weigh 6g of NASC and 12g of ACG into a reaction container, then add 50ml of acetonitrile solvent, stir at room temperature until NASC and ACG are completely dissolved, then add 0.36g of IRGACURE-2959 to the mixture, stir again, and initiate the polymerization reaction under 365nm ultraviolet light with a handheld UV lamp (model WFH-204B) and maintain illumination for 40min. Then filter the mixture to collect the filter cake, and wash the filter cake with 150ml of distilled water three times, 50ml each time, and then wash the filter cake with 150ml of ethanol three times, 50ml each time, and dry it in vacuum at room temperature to obtain the additive. The structural composition of the macromolecule was tested using a hydrogen nuclear magnetic resonance spectrometer (deuterated DMSO as solvent), as shown in the attached Figure 1 As shown in the figure, the characteristic peak of carbon-carbon double bond no longer appears in the spectrum, and the characteristic absorption peaks of carboxyl and amide groups are retained, indicating that the two monomers have achieved copolymerization. The number average molecular weight Mn of the PNASC-PACG copolymer tested by gel permeation chromatography (GPC) is about 32,000, and the polydispersity coefficient PID is 1.49, indicating that the monomer has undergone polymerization.
[0057] (2) Preparation of anti-fog and heat-resistant polyurethane optical resin
[0058] Weigh 52g of XDI isocyanate in a stirred reaction vessel and add 0.02g of catalyst dibutyltin dichloride, 0.05g of UV absorber UV-329, 0.12g of internal release agent, and 5g of PNASC-PACG polymer additive in sequence. After dissolving, add 48g of 2,3-dithio (2-mercapto) -1-propanethiol, stir and filter the mixture through a filter membrane and inject it into a special mold for lens processing (the liquid level in the mold is about 7mm), degas for 1 hour under the conditions of less than or equal to 2kPa and 25℃, and the pore size of the filter membrane is 1μm. After degassing, it is heated from 25℃ to 120℃ in an oven to polymerize and cure, and the heating rate is set to 0.2℃ / min. When the oven temperature reaches 120℃, maintain it for 2 hours to obtain a cured sample, and the subsequent sample is naturally cooled to room temperature. After secondary curing at room temperature for 48h, demolding to obtain an optical resin material. The obtained optical resin material is demolded and then subjected to subsequent optical performance tests, thermal performance tests and anti-fog performance tests.
[0059] Example 2
[0060] An anti-fog and heat-resistant polyurethane optical resin containing 2.5 wt % PNASC-PACG copolymer (the monomer molar ratio of NASC to ACG is 1:5) was prepared.
[0061] (1) Synthesis of PNASC-PACG polymer additive
[0062] Weigh 3g of NASC and 15g of ACG into a reaction container, add 50ml of acetonitrile solvent, stir at room temperature until NASC and ACG are completely dissolved, then add 0.36g of IRGACURE-2959 to the mixture, stir again, initiate with a handheld UV lamp (model WFH-204B) under 365nm UV light and maintain illumination for 40min to complete the polymerization reaction. Then filter the mixture to collect the filter cake, wash the filter cake with 150ml of distilled water three times, 50ml each time, then wash the filter cake with 150ml of ethanol three times, 50ml each time, and dry under vacuum at room temperature to obtain the additive.
[0063] (2) Preparation of anti-fog and heat-resistant polyurethane optical resin
[0064] Weigh 52g of XDI isocyanate in a stirred reaction vessel and add 0.02g of catalyst dibutyltin dichloride, 0.05g of UV absorber UV-329, 0.12g of internal release agent, and 2.5g of PNASC-PACG polymer additive in sequence. After dissolving, add 48g of 2,3-dithio (2-mercapto) -1-propanethiol, stir, filter the mixture through a filter membrane, and inject it into a special mold for lens processing (the liquid level in the mold is about 7mm), degas for 1 hour under the conditions of less than or equal to 2kPa and 25℃, and the pore size of the filter membrane is 1μm. After degassing, it is heated from 25℃ to 120℃ in an oven to polymerize and cure, and the heating rate is set to 0.2℃ / min. When the oven temperature reaches 120℃, maintain it for 2 hours to obtain a cured sample, and the subsequent sample is naturally cooled to room temperature. After secondary curing at room temperature for 48h, demolding to obtain an optical resin material. The obtained optical resin material is demolded and then subjected to subsequent optical performance tests, thermal performance tests and anti-fog performance tests.
[0065] Example 3
[0066] An anti-fog and heat-resistant polyurethane optical resin containing 1 wt % PNASC-PACG copolymer (the monomer molar ratio of NASC to ACG is 1:8) was prepared.
[0067] (1) Synthesis of PNASC-PACG polymer additive
[0068] Weigh 2g of NASC and 16g of ACG into a reaction container, add 50ml of acetonitrile solvent, stir at room temperature until NASC and ACG are completely dissolved, then add 0.36g of IRGACURE-2959 to the mixture, stir again, initiate with a handheld UV lamp (model WFH-204B) under 365nm UV light and maintain illumination for 40min to complete the polymerization reaction. Then filter the mixture to collect the filter cake, wash the filter cake with 150ml of distilled water three times, 50ml each time, then wash the filter cake with 150ml of ethanol three times, 50ml each time, and dry under vacuum at room temperature to obtain the additive.
[0069] (2) Preparation of anti-fog and heat-resistant polyurethane optical resin
[0070] Weigh 52g of XDI isocyanate in a stirred reaction vessel and add 0.02g of catalyst dibutyltin dichloride, 0.05g of UV absorber UV-329, 0.12g of internal mold release agent, and 1g of PNASC-PACG polymer additive in sequence. After dissolving, add 48g of 2,3-dithio (2-mercapto)-1-propanethiol, stir, filter the mixture through a filter membrane, and inject it into a special mold for lens processing (the liquid level in the mold is about 7mm), degas for 1 hour under the conditions of less than or equal to 2kPa and 25℃, and the pore size of the filter membrane is 1μm. After degassing, it is heated from 25℃ to 120℃ in an oven to polymerize and cure, and the heating rate is set to 0.2℃ / min. When the oven temperature reaches 120℃, maintain it for 2 hours to obtain a cured sample, and the subsequent sample is naturally cooled to room temperature. After secondary curing at room temperature for 48h, demolding to obtain an optical resin material. The obtained optical resin material is demolded and then subjected to subsequent optical performance tests, thermal performance tests and anti-fog performance tests.
[0071] Example 4
[0072] An anti-fog and heat-resistant polyurethane optical resin containing 4 wt % PNASC-PACG copolymer (the monomer molar ratio of NASC to ACG is 2:1) was prepared.
[0073] (1) Synthesis of PNASC-PACG polymer additive
[0074] Weigh 12g of NASC and 6g of ACG into a reaction container, add 50ml of acetonitrile solvent, stir at room temperature until NASC and ACG are completely dissolved, then add 0.36g of IRGACURE-2959 to the mixture, stir again, initiate with a handheld UV lamp (model WFH-204B) under 365nm UV light and maintain illumination for 40min to complete the polymerization reaction. Then filter the mixture to collect the filter cake, wash the filter cake with 150ml of distilled water three times, 50ml each time, then wash the filter cake with 150ml of ethanol three times, 50ml each time, and dry under vacuum at room temperature to obtain the additive.
[0075] (2) Preparation of anti-fog and heat-resistant polyurethane optical resin
[0076] 47.8 g H was weighed into a stirred reaction vessel. 6 XDI isocyanate, then add 0.05g of catalyst dibutyltin dichloride, 0.05g of ultraviolet absorber UV-329, 0.12g of internal release agent, and 4g of PNASC-PACG polymer additive in sequence. After dissolving, add 28.4g of 2,3-dithio (2-mercapto)-1-propanethiol and 23.8g of pentaerythritol tetrakis (3-mercaptopropionic acid), stir, filter the mixture through a filter membrane, and inject it into a special mold for lens processing (the liquid level in the mold is about 7mm), degas for 1 hour at 2kPa or less and 25℃, and the pore size of the filter membrane is 1μm. After degassing, it is heated from 25℃ to 120℃ in an oven to polymerize and cure, and the heating rate is set to 0.1℃ / min. When the oven temperature reaches 120°C, maintain it for 2 hours to obtain a cured sample, and then the sample is naturally cooled to room temperature, and after secondary curing at room temperature for 48 hours, demolding to obtain an optical resin material. The obtained optical resin material is demolded and then subjected to subsequent optical performance tests, thermodynamic performance tests, and anti-fog performance tests.
[0077] Example 5
[0078] An anti-fog and heat-resistant polyurethane optical resin containing 7 wt % PNASC-PACG copolymer (the monomer molar ratio of NASC to ACG is 5:1) was prepared.
[0079] (1) Synthesis of PNASC-PACG polymer additive
[0080] Weigh 15g of NASC and 3g of ACG into a reaction container, add 50ml of acetonitrile solvent, stir at room temperature until NASC and ACG are completely dissolved, then add 0.36g of IRGACURE-2959 to the mixture, stir again, initiate with a handheld UV lamp (model WFH-204B) under 365nm UV light and maintain illumination for 40min to complete the polymerization reaction. Then filter the mixture to collect the filter cake, wash the filter cake with 150ml of distilled water three times, 50ml each time, then wash the filter cake with 150ml of ethanol three times, 50ml each time, and dry under vacuum at room temperature to obtain the additive.
[0081] (2) Preparation of anti-fog and heat-resistant polyurethane optical resin
[0082] 23 g of hexamethylene diisocyanate (HDI) and 15.5 g of cyclohexane dimethylene diisocyanate (HDI) were weighed into a stirred reaction vessel. 6 A mixed isocyanate consisting of 11.5g of isophorone diisocyanate (IPDI), 1.5g of dibutyltin dichloride catalyst, 0.02g of UV absorber UV-329, 0.12g of internal mold release agent, and 7g of PNASC-PACG polymer additive were added in sequence. After dissolving, 38g of 2,3-dithio (2-mercapto)-1-propanethiol and 12g of pentaerythritol tetrakis (3-mercaptopropionic acid) were added. After stirring, the mixed solution was filtered through a filter membrane and injected into a special mold for lens processing (the liquid level in the mold was about 7mm), and degassed for 1 hour at 2kPa or less and 25°C. The pore size of the filter membrane was 1μm. After degassing, it was heated from 25°C to 120°C in an oven to polymerize and cure, and the heating rate was set to 0.1°C / min. When the oven temperature reaches 120°C, maintain it for 2 hours to obtain a cured sample, and then the sample is naturally cooled to room temperature, and after secondary curing at room temperature for 48 hours, demolding to obtain an optical resin material. After demolding, the obtained optical resin material is subjected to subsequent optical performance tests, thermal performance tests, and anti-fog performance tests.
[0083] Example 6
[0084] An anti-fog and heat-resistant polyurethane optical resin containing 9 wt % PNASC-PACG copolymer (the monomer molar ratio of NASC to ACG is 8:1) was prepared.
[0085] (1) Synthesis of PNASC-PACG polymer additive
[0086] Weigh 16g of NASC and 2g of ACG into a reaction container, add 50ml of acetonitrile solvent, stir at room temperature until NASC and ACG are completely dissolved, then add 0.36g of IRGACURE-2959 to the mixture, stir again, initiate with a handheld UV lamp (model WFH-204B) under 365nm UV light and maintain illumination for 40min to complete the polymerization reaction. Then filter the mixture to collect the filter cake, wash the filter cake with 150ml of distilled water three times, 50ml each time, then wash the filter cake with 150ml of ethanol three times, 50ml each time, and dry under vacuum at room temperature to obtain the additive.
[0087] (2) Preparation of anti-fog and heat-resistant polyurethane optical resin
[0088] Weigh 52g of XDI isocyanate in a stirred reaction vessel and add 0.02g of catalyst dibutyltin dichloride, 1.2g of ultraviolet absorber UV-329, 1.5g of internal release agent, and 9g of PNASC-PACG polymer additive in sequence. After dissolving, add 48g of 2,3-dithio (2-mercapto) -1-propanethiol, stir and filter the mixture through a filter membrane and inject it into a special mold for lens processing (the liquid level in the mold is about 7mm), degas for 1 hour under the conditions of less than or equal to 2kPa and 25℃, and the pore size of the filter membrane is 1μm. After degassing, it is heated from 25℃ to 120℃ in an oven to polymerize and cure, and the heating rate is set to 0.2℃ / min. When the oven temperature reaches 120℃, maintain it for 2 hours to obtain a cured sample, and the subsequent sample is naturally cooled to room temperature. After secondary curing at room temperature for 48h, demolding to obtain an optical resin material. The obtained optical resin material is demolded and then subjected to subsequent optical performance tests, thermal performance tests and anti-fog performance tests.
[0089] Comparative Example 1: Preparation of polyurethane optical resin material without PNASC-PACG Compared with Example 1, this comparative example does not add the homemade PNASC-PACG copolymer, and the other sample types and amounts, experimental steps and reaction time are the same as those in Example 1.
[0090] Comparative Example 2: Preparation of polyurethane optical resin material without PNASC-PACG Compared with Example 4, this comparative example does not add the homemade PNASC-PACG copolymer, and the other sample types and amounts, experimental steps and reaction time are the same as those in Example 4.
[0091] In order to further illustrate the technical advancement of the present invention, experimental tests are now conducted on the indicators of different embodiments and comparative examples. The test performance data of the optical resin lens materials of embodiments 1-6 and comparative examples 1-2 are summarized in Table 1.
[0092] Table 1 Performance parameters of optical resin lens materials in Examples 1-6 and Comparative Examples 1-2
[0093] sample YI value Transmittance / % Tg / ℃ Water contact angle / ° Cold fog method level Water bath mist grade Example 1 1.68 83.81 115.24 11 Level 1 Level 1 Example 2 1.70 83.49 107.31 12 Level 1 Level 1 Example 3 1.69 83.23 95.28 15 Level 1 Level 1 Example 4 1.23 86.33 131.16 17 Level 1 Level 1 Example 5 1.14 85.96 113.29 29 Level 1 Level 2 Example 6 1.74 82.41 123.87 38 Level 1 Level 2 Comparative Example 1 1.68 83.65 87.03 102 Level 4 Level 5 Comparative Example 2 1.21 86.18 104.67 104 Level 4 Level 5
[0094] According to the results of Examples 1-6 and Comparative Examples 1-2, the PNASC-PACG additive synthesized by the present invention not only significantly improves the surface hydrophilicity of the polyurethane optical resin but also improves the thermal properties of the resin, while having no negative impact on the transmittance and YI of the optical resin.
[0095] The above-described embodiments are only some embodiments of the present invention, but not all embodiments. Under the guidance of this specification, those skilled in the art may make some modifications or adjustments to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. An anti-fog heat-resistant polyurethane optical resin, characterized in that: The resin comprises the following components: isocyanate, a polythiol compound, a catalyst, an ultraviolet absorber, a polymer auxiliary agent and a release agent, wherein the polymer auxiliary agent is a copolymer obtained by polymerizing acryloyl ureaamine and acryloyl glycine, and the molar ratio of acryloyl ureaamine to acryloyl glycine is 1:10-10:1; The addition amount of the polymer auxiliary agent is 0.1wt%-10wt%, based on the total weight of the isocyanate and the polythiol compound.
2. The optical resin according to claim 1, characterized in that: In the polymer auxiliary agent, the molar ratio of acryloyl ureaamine to acryloyl glycine is 1:6-6:
1.
3. The optical resin according to claim 2, characterized in that: In the polymer auxiliary agent, the molar ratio of acryloyl ureaamine to acryloyl glycine is 1:3-3:
1.
4. The optical resin according to claim 1, characterized in that: The structural formula of the acryl urea amine is: The structural formula of the acryloylglycine is:
5. The optical resin according to claim 1, characterized in that: The polymerization reaction of acryloyl ureaamine and acryloyl glycine is carried out in the presence of an initiator, which is a free radical initiator.
6. The optical resin according to claim 5, characterized in that: The free radical initiator is selected from an organic peroxide compound initiator, an azo compound initiator, a redox system initiator or a photosensitive initiator.
7. The optical resin according to claim 6, characterized in that: The organic peroxide compound initiator is selected from dibenzoyl peroxide or peroxydicarbonate, the azo compound initiator is selected from azobisisobutyronitrile or azobisisoheptanenitrile, the redox system initiator is selected from an organic oil-soluble redox system formed by a peroxide acyl compound and a tertiary amine compound, and the photosensitive initiator is selected from the photoinitiator IRGACURE-2959.
8. The optical resin according to claim 6, characterized in that: The free radical initiator is a photosensitive initiator.
9. The optical resin according to claim 5, characterized in that: The added amount of the initiator is 1%-3% of the total mass of the acryloyl urea amine and acryloyl glycine monomers.
10. The optical resin according to claim 9, characterized in that: The added amount of the initiator is 1.5-2.5% of the total weight of the acryloyl urea amine and acryloyl glycine monomers.
11. The optical resin according to claim 1, characterized in that: The addition amount of the polymer auxiliary agent is 2wt%-8wt%, based on the total weight of the isocyanate and the polythiol compound.
12. The optical resin according to claim 11, characterized in that: The addition amount of the polymer auxiliary agent is 3wt%-6wt%, based on the total weight of the isocyanate and the polythiol compound.
13. The optical resin according to claim 1, characterized in that: The isocyanate is selected from aliphatic, alicyclic or aromatic isocyanates.
14. The optical resin according to claim 13, characterized in that: The isocyanate is selected from one or a combination of two or more of toluene diisocyanate, diphenylmethane diisocyanate, isophorone diisocyanate, hexamethylene diisocyanate, dicyclohexylmethane diisocyanate, naphthalene diisocyanate, dimethylbiphenyl diisocyanate, 1,4-cyclohexane diisocyanate, p-phenylene diisocyanate, tetramethyl meta-xylylene diisocyanate, trimethyl-1,6-hexamethylene diisocyanate, xylylene diisocyanate, cyclohexane dimethylene diisocyanate and norbornane diisocyanate.
15. The optical resin according to claim 14, characterized in that: The isocyanate is selected from xylylene diisocyanate or cyclohexane dimethylene diisocyanate.
16. The optical resin according to claim 15, characterized in that: The isocyanate is selected from xylylene diisocyanate.
17. The optical resin according to claim 1, characterized in that: The polythiol compound is selected from ethylene glycol dimercaptoacetate, 1,2-bis(2-mercaptoethoxy)ethane, di(thioglycolic acid)-1,4-butylene glycol, trimethylolpropane tris(3-mercaptopropionate), trimethylolpropane tris(2-mercaptoacetate), pentaerythritol tetramercaptoacetate, 2,3-dithio(2-mercapto)-1-propanethiol, pentaerythritol tetrakis(3-mercaptopropionic acid) and a combination of one or two or more thereof.
18. The optical resin according to claim 17, characterized in that: The polythiol compound is selected from 2,3-dithio(2-mercapto)-1-propanethiol or pentaerythritol tetrakis(3-mercaptopropionic acid) ester.
19. The optical resin according to claim 18, characterized in that: The polythiol compound is 2,3-dithio(2-mercapto)-1-propanethiol.
20. The optical resin according to claim 1, characterized in that: The molar ratio of the -NCO group of the isocyanate to the -SH group of the polythiol is (0.8-1.5):
1.
21. The optical resin according to claim 20, characterized in that: The molar ratio of the -NCO group of the isocyanate to the -SH group of the polythiol is (0.9-1.1):
1.
22. The optical resin according to claim 1, characterized in that: The catalyst is selected from an organic metal catalyst, and the metal elements contained include one or more of tin, potassium, lead, mercury and zinc.
23. The optical resin according to claim 22, characterized in that: The catalyst is selected from tin metal catalysts.
24. The optical resin according to claim 1, characterized in that: The catalyst is added in an amount of 0.01 to 2.0 wt % based on the total mass of the isocyanate component and the polythiol compound.
25. The optical resin according to claim 24, characterized in that: The catalyst is added in an amount of 0.015 to 1.0 wt % based on the total mass of the isocyanate component and the polythiol compound.
26. The optical resin according to claim 1, characterized in that: The ultraviolet absorber is a benzophenone, triazine or benzotriazole ultraviolet absorber, and the added amount is 0.01 to 2.0 weight % based on the total mass of the isocyanate component and the polythiol compound.
27. The optical resin according to claim 26, characterized in that: The added amount of the ultraviolet absorber is 0.03 to 1.0 wt % based on the total mass of the isocyanate component and the polythiol compound.
28. The optical resin according to claim 1, characterized in that: The release agent is a phosphate-based release agent, and the added amount is 0.01 to 3.0 weight % based on the total mass of the isocyanate component and the polythiol compound.
29. The optical resin according to claim 28, characterized in that The addition amount of the release agent is 0.08 to 1.0 wt % based on the total mass of the isocyanate component and the polythiol compound.
30. A method for preparing an optical resin according to any one of claims 1 to 29, characterized in that: The optical resin is obtained by mixing isocyanate, polythiol compound, polymer auxiliary agent, catalyst, ultraviolet absorber and release agent, vacuum degassing and heating to cure.
31. The preparation method according to claim 30, characterized in that: After the raw materials are mixed and filtered through a filter membrane, they are injected into a special mold for lens processing. They are degassed for 0.5-1.5 hours at room temperature and a pressure of ≤2kPa, and then restored to normal pressure. They are then slowly heated from low temperature to high temperature for curing. The sample is naturally cooled to room temperature, and after secondary curing at room temperature for 24-72 hours, they are demolded to obtain optical materials.
32. The preparation method according to claim 31, characterized in that: Curing from low temperature heating to high temperature is as follows: heating from room temperature to 100-130°C, setting the heating rate to 0.1-0.2°C / min, polymerizing and curing, and maintaining the temperature at 100-130°C for 1-3 hours.
Citation Information
Patent Citations
Supramolecular copolymerized hydrogel and preparation method thereof
CN112521550A
High-modulus supramolecular polymer hydrogel based on urea amine and preparation method of high-modulus supramolecular polymer hydrogel
CN112521625A
High-strength super-molecular hydrogel, preparation method therefor and application of high-strength super-molecular hydrogel
CN106397646A
Anti-blue-light polyurethane optical resin material
CN111303612A